Effect of Rhythmic Craniocerebral Hypothermia on Neurohumoral Mechanisms of Cyclic Process Regulation in Reproductive System - Ershova, O. V. (Problems of Cryobiology and Cryomedicine, 2007)
The application of rhythmic craniocerebral hypothermia (RCCH) under disorded cyclic processes of reproductive system in female rats was established as enabling to directly correct pathological processes, developing under emotional-pain stress (EPS). During RCCH the changes of serotonin secretion in epiphysis and hypothalamus occur, thereby indicating to the expediency of RCCH method application to correct disorders caused by functional dysfunction of neurotransmitter system. When using RCCH with the aim to correct the disorders of cyclic processes in female rat reproductive systems after EPS a directed tendency of hormonal level normalisation in peripheral blood is also determined.